Asuhan Keperawatan Pemenuhan Oksigenasi dengan Posisi Semi Fowler dan Inhalasi dalam Mengatasi Bersihan Jalan Napas di Instalasi Gawat Darurat - indri maria sihombing; Mia Atlantic; Ns. Cicelia Ernawati Rahayu (Jurnal Kesehatan STIKes Sumber Waras, 2025)
Background: Pneumonia is characterized by fever and increased phlegm production which can inhibit the effectiveness of airway clearance, causing shortness of breath. Data from the 2023 Indonesian Health Survey (SKI) recorded 877,531 cases of pneumonia in all age groups, the increasing number of cases requires more comprehensive care to prevent complications, namely respiratory failure. The need for oxygen is one of the basic demands that people have to maintain physiological and psychological balance. One of the components of gas, oxygen is very important in the metabolic process that keeps all body cells alive. Objective: To obtain an overview of nursing care in meeting oxygenation needs through the use of the semi-Fowler position and inhalation as an effort to overcome airway clearance disorders Research Method: Case study conducted on 2 respondents. The intervention given was the provision of a semi-Fowler position and inhalation in the Emergency Installation of Sumber Waras Hospital. Research Results: after the intervention of providing a semi-fowler position and inhalation during the Emergency Room, both respondents experienced an increase in oxygen saturation of around 3% -6%, shortness of breath decreased from 25x/minute to 21x/minute, and were able to expel 2-3cc of thick, green, and smelly sputum. Conclusion: Providing a semi-fowler position and inhalation has been proven to reduce shortness of breath, expel sputum and increase oxygen saturation.